Dairy animal welfare: Review on scientific concept and assessment methodologies (Indian Journal of Animal Production and Management, 2016)
Welfare of the dairy cows is one of the major  concerns in most of the developing countries due  its impact on the productivity of cows, health of the  animal, climate as well as on public health in the  present day context. Consumers are increasingly  more aware of the impact of dairy cow welfare  on public health, dairy product safety and health  propriety as well as environmental protection. As  a result, to-day more and more consumers are  oriented towards buying products from animals  whose welfare is not threatened and where it is  guaranteed that the products from farm animals are  in the line with the standards of good husbandry  practices in the farm.